PERKEMBANGAN PROSES PEMBUATAN BIODIESEL SEBAGAI BAHAN BAKAR NABATI (BBN) - Joelianingsih .; Armansyah H Tambunan; Hiroshi Nabetani; Yasuyuki Sagara; Kamaruddin Abdullah (PERTETA, 2006)
ABSTRACT As energy dernands increase and fossil fuel reservas are limited, research is directed towards alternative renewable fluls. A potential diesel fuel substitusi is biodiesel, obtained from fatty acids methyl esters (FAME) and produced by the transesterfication reaction of triglyceride or free fatty acid (FFA) of vegetable oils with short-chain alcohol, mainly methanol. Most of the currently of alcohol. Although the removal of the excess alcohol can be easily achieved by distillation, however the removal of catlyst and the by-product formed from its reaction with the reactants is complicated while several methode for glycerol purification have been reported. The disadvantages resulting from the use of a catalyst and itsremoval from theproducts can beeliminated if a non-catalytic reaction of the vegetable oils with alcohol can be realized and a simpler and cheaper process can be developed.indonesia has the opportunity to expand oil palm and other plantations such as jatropha curcas (jarak pagar)in order to provide sufficient amount of crude oil for development of biodiesel industry. Keyword: biodiesel, vegetable oil, renewable source of energy, catalyst, non-catalytic, transesterfication Diterima: 6 April 2006; Disetujui: 19 Juli 2006